Public policy, food markets, and household coping strategies in Bangladesh: lessons from the 1998 floods - del Ninno, Carlo; Dorosh, Paul A.; Smith, Lisa C. (International Food Policy Research Institute, 2003)
Flooding is a normal part of the ecology of Bangladesh. The 1998 flood was especially serious because of its depth and duration. At its peak, the flood covered two-thirds of the country, causing severe damage to the rice crop and threatening the food security of millions of households. Total rice production losses exceeded 2 million tons—about 10 percent of annual consumption. In sharp contrast to earlier flood disasters, particularly that of 1974, no major food crisis occurred. Instead, large-scale, private-sector imports, made possible by trade liberalization in the early 1990s, stabilized rice markets. Government food transfers to poor households also limited the impact of the flood on household access to food. This paper sheds light on the contribution of price stabilization to household food security following a major natural shock through estimates of the impact of rice prices and other factors on calorie consumption in 1998 and 1999. More broadly, the paper examines the components of the public and private response that prevented a major food crisis. -- from Authors' Abstract